The Images of Patron Saints in the Court Culture and Art of Renaissance Ferrara: Between Sacred and Courtesy - Churkina, Daria A. (Actual Problems of Theory and History of Art, 2019)
In the 15th–16th centuries, the court of Ferrara was famous throughout Europe for its luxury and wealth because of the “policy of magnificence” methodically conducted by the Este rulers. One of the important principles of the Este’s cultural policy was the preservation of the late medieval traditions, which were expressed in customs, literature and fine arts of the Ferrara court. Sometimes the images of the late medieval culture became vehicles for the new humanistic ideas. The Ferrara’s patron saints — St. George and St. Maurelius — were considered the symbols of succession from the Middle Ages to the Modern Time for the city. However, already during the Early Renaissance, the figures of these saints gradually became associated not only with the city, but also with the members of the ruling dynasty. It is important to take into account that the “policy of magnificence”, conducted by the Estensi, was not limited solely to secular culture. On the contrary, piety and church patronage were considered the most important virtues of a monarch. Therefore St. George, who was regarded as embodiment of an ideal Christian knight, probably was simultaneously associated with the ruler of Ferrara, while St. Maurelius could personify the bishop, whose throne was also often occupied by the Este family members or those of their courtiers’ families. The iconographic and iconological analysis of these saints’ images in the visual arts and culture of Renaissance Ferrara allows us to demonstrate synthesis of courtly, Christian and humanistic components of the “policy of magnificence” of the Este dynasty.
Keywords: Ferrara; Early Renaissance; iconography; court culture; Saint George; Saint Maurelius